EFEKTIFITAS BANTUAN SOSIAL DALAM PENANGGULANGAN KEMISKINAN DI TENGAH PERLAMBATAN EKONOMI INDONESIA DENGAN PENDEKATAN NON-PARAMETRIK - Palupi Lindiasari Samputra; Aji Wahyu Ramadhani (Jurnal Perspektif Ekonomi Darussalam (Darussalam Journal of Economic Perspec, 2019)
This study aims to analyze the relationship and influence of social assistance on the number of poor people in Indonesia. There is a control variable as a comparison, namely; the number of people who work alone and work as laborers, central government debt and economic growth. The research method uses a quantitative approach with non-parametric statistics with annual data (2007-2017) and elasticity is used to measure the amount of change in the number of poor people due to additional social assistance. Pearson Moment Product and Rank Spearman correlation test to examine the relationship of each variable (number of people who work alone and work as laborers, central government debt and economic growth) to the number of poverty in Indonesia. The results of non-parametric statistics show that there is a very strong relationship between social assistance (National Health Insurance-Benefit Beneficiary Recipients (JKN-PBI) and Prosperous Rice (Rastra), and strong (Family Hope Program (PKH)) for the number of poor people. negative indicates that social assistance can significantly reduce the amount of poverty, with the strongest impact being the PBI program.There is a strong relationship between debt and working as a laborer on the number of poor people. The slowdown in economic growth is proven to be unrelated to the number of poor people. the biggest decrease in the number of poor people is the JKN-PBI program (-0.16), Rastra (-0.15) and PKH (-0.06). The additional employment as laborers has the highest effectiveness level of -0, 34. Government debt is needed to reduce the number of poor people by -0.16, which means that in the middle of declining oak On the other hand, the amount of poverty in Indonesia can be reduced through social assistance programs, the creation of jobs as laborers and government debt allocated to productive activities and economic activities that directly affect the poor and vulnerable to poverty. Keywords: Social assistance programs, Economics growth, Debt, Poverty, Laborers, Effectiveness Abstrak Penelitian ini bertujuan untuk menganalisis hubungan dan pengaruh bantuan sosial terhadap jumlah penduduk miskin di Indonesia.  Terdapat variabel kontrol sebagai pembanding yaitu; jumlah orang yang bekerja sendiri dan bekerja sebagai buruh, utang pemerintah pusat dan pertumbuhan ekonomi. Metode penelitian menggunakan pendekatan kuantitatif dengan statistik non-parametrik, data tahunan (2007-2017) dan elastisitas digunakan untuk mengukur besaran perubahan jumlah penduduk miskin akibat tambahan bantuan sosial. Uji korelasi Pearson Moment Product dan Rank Spearman untuk menguji hubungan masing-masing variabel (jumlah orang yang bekerja sendiri dan bekerja sebagai buruh, utang pemerintah pusat dan pertumbuhan ekonomi) terhadap jumlah kemiskinan di Indonesia.  Hasil penelitian menunjukkan terdapat hubungan yang sangat kuat antara bantuan sosial (Jaminan Kesehatan Nasional-Penerima Bantuan Iuran (JKN-PBI) dan Beras Sejahtera (Rastra), dan Program Keluarga Harapan (PKH) terhadap jumlah penduduk miskin. Tanda negatif menunjukkan bantuan sosial dapat menurunkan jumlah kemiskinan secara signifikan, dengan dampak terkuat adalah program PBI.  Terdapat hubungan kuat antara hutang dan bekerja sebagai buruh terhadap jumlah penduduk miskin. Perlambatan pertumbuhan ekonomi terbukti tidak  berhubungan dengan jumlah penduduk miskin. Hasil perhitungan elastisitas menunjukkan efektifitas bantuan sosial terhadap penurunan jumlah penduduk miskin paling besar adalah program JKN-PBI  (-0,16), Rastra (-0,15) dan PKH (-0,06).  Tambahan lapangan kerja sebagai buruh memiliki tingkat efektifitas yang paling tinggi sebesar -0,34.  Hutang pemerintah dibutuhkan untuk menekan jumlah penduduk miskin sebesar -0,16. Artinya, di tengah perlambatan ekonomi, jumlah kemiskinan di Indonesia dapat ditekan melalui program bantuan sosial, penciptaan lapangan kerja sebagai buruh dan hutang pemerintah dialokasikan untuk kegiatan produktif dan kegiatan ekonomi yang berdampak langsung kepada penduduk miskin dan rentan miskin.